Body Composition and Handgrip Strength for Early Detection of Sarcopenia in Employees - Iriyanti Harun; Stephanie Melia; Iriyani Harun (Sarana Ilmu Indonesia (Salnesia), 2026)
Sarcopenia is a degenerative disorder characterized by the decline of skeletal muscle mass, strength, and function, which is now emerging among the sedentary productive-age population. Early detection of this condition can be practically and affordably achieved through body composition analysis and handgrip strength measurement.This study aimed to investigate the correlation between body composition parameters and handgrip strength among the staff at Immanuel Health Institute. This study used a cross-sectional analytic study design on 75 employees selected using total sampling. Body mass index (BMI), body fat percentage, visceral fat, and skeletal muscle mass were measured using a Bioelectrical Impedance Analysis (BIA) scale, while handgrip strength was assessed with a digital hand dynamometer. The analysis revealed a positive correlation between skeletal muscle mass and handgrip strength (r = 0.602, p < 0,001), while a significant negative correlation was found with body fat percentage (r = -0.536, p < 0.001). Neither BMI (r = 0.033, p = 0.778) nor visceral fat (r = 0.175, p = 0.133) demonstrated a significant relationship. Multiple linear regression analysis identified skeletal muscle mass as the only significant predictor of handgrip strength (β = 2.176, p < 0.001), with an adjusted R² value of 0.530. In conclusion, skeletal muscle mass was a key predictor of handgrip strength among employees. Skeletal muscle mass using BIA in conjunction with handgrip strength was suggested as an effective and practical method for early detection of sarcopenia in the productive workforce.